2014
DOI: 10.4103/2230-8210.129107
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of sexual dysfunction in women with type 2 diabetes

Abstract: Background:Sexual dysfunction is a common complication of diabetes that adversely affects their quality of life. Its prevalence is known to be higher in diabetic men with and it is estimated to affect 20-85% of patients but the problem is probably less common in diabetic women. This study investigated the prevalence of sexual dysfunction and its risk factors among women with diabetes.Materials and Methods:This descriptive-analytic study was performed during May 2012 to Feb 2013 at Diabetes clinic of Shahid Beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 21 publications
3
32
0
Order By: Relevance
“…Only 9 studies looked specifically at MS [2,25,26,27,28,29,30,31,32]. The remaining included data about components of MS [2,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Only 9 studies looked specifically at MS [2,25,26,27,28,29,30,31,32]. The remaining included data about components of MS [2,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58]. …”
Section: Resultsmentioning
confidence: 99%
“…Total 35 studies met the inclusion criteria (Table 1, 2) [2,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58]. Sixteen studies were classified as case-control studies [2,28,29,32,37,38,39,41,42,44,47,49,51,52,54,57] and the rest as observational/cross-sectional studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Results showed that 53.6% of women had sexual dysfunction and there was a significant relation between albuminuria and sexual dysfunction ( p = 0.001) and also retinopathy and sexual dysfunction ( p = 0.007) [12]. …”
Section: Introductionmentioning
confidence: 99%
“…Vafaeimanesh et al presented significant correlations between sexual dysfunctions and retinopathy and nephropathy. They suggested that chronic problems, such as retinopathy and nephropathy can be considered as risk factors for sexual dysfunction (21,29).…”
Section: Discussionmentioning
confidence: 99%